Prevalence of Microplastic Pollution in Freshwater Ecosystem: A Case Study of Thal Canal - Syed Daniyal Kazim Naqvi; Batool, Aniqa; Muhammad Asad Ghufran; Rauf, Zeeshan; Syeda Umme Kulsoom; Iqra Parveen; Asif Ali Shah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Microplastic pollution in the aquatic ecosystems is a hot global debate due to wide spread effects on human life and environment. This study aims to identify microplastic pollution presence in the Main Line (ML) Thal canal, its distributaries and provide an overall estimation of microplastics concentration in surface water of Thal Canal. Six major sampling points at ML canal and distributaries were assessed for microplastic prevalence out of which five locations showed microplastic contamination. Size, structure and type of microplastic were assessed using light microscopy and FTIR. The study provided baseline information about the prevalence of microplastics in Thal Canal and evaluated their categories according to their size, color and type of polymers. Microplastics concentration in the canal ranged from 6.4 ± 0.5 to 8.8 ± 0.5 particles/m³. Films, mostly transparent in coloration, were the most prominent microplastic type appeared in this study. Polyethylene with 55% presence was the most prevalent type of microplastics found in the canal and the distributaries. This study provides a better understanding of the extent of microplastic pollution assessment in Thal canal with equal emphasis on Microplastic presence in distributaries which may be beneficial in identifying the introduction of microplastics at sources.